Identifying barriers to early presentation in patients with locally advanced breast cancer (LABC) in Northern Singapore : qualitative study - Ng, Ding Yi (2021)
Introduction: Breast cancer is the leading cause of death in Singaporean women, with advanced stage rendering a poorer prognosis. This study aims to explore the barriers to early presentation, information needs and sources in patients with locally advanced breast cancer (LABC). Materials & methods: A convenience sample of patients who presented with locally advanced breast cancer to the Department of General Surgery in a teaching tertiary hospital were recruited for the study. We conducted semi-structured interviews face to face with the recruited patients. We recorded the interviews, transcribed them verbatim and analysed using thematic content analysis. Results: Twenty-three participants were recruited of which 12 were Chinese and 11 were Malay women. Mean age was 60 years (± 13 SD). The most common knowledge barrier resulting in delay was the misconception that a breast lump must be painful to be malignant. Other knowledge barriers include the lack of knowledge and misinformation from the internet or other social media platforms. Some perceived barriers include fear of diagnosis, fear of treatment and fear of imposing financial burden on family members. A significant proportion of participants were also not aware of a national breast screening programme. Conclusions: Our study has found that barriers to early presentation of women with locally advanced breast cancer remain similar and have persisted over the years despite targeted efforts. There is a need for a rethink of existing strategies and to develop new innovative ways to reach out to this group of patients.